Sistem Pembobotan Berdasarkan Teknik Analisis Korelasi Untuk Penerimaan Siswa Baru Menggunakan Metode SAW - Nimas Dian Fitria; Aji Prasetya Wibawa (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
New Student Admission (PSB) is an annual program held by the school to get students, according to the criteria desired by the school. One of alternatif method to determine the ranking of prospective new students is to use the SAW (Simple Additive Weighting) method. To reduce the subjectivity that arises in the use of the SAW method, a correlation analysis technique is used which is useful for knowing the level of correlation of each criterion on new student admissions. Based on the results of the research, it was found that the parents' income criteria had the highest weight (0.851), followed by math scores (0.845), English scores (0.831), physics scores (0.577), physical ability (0.539), and finally student interest (0.282). Meanwhile, the results based on ranking using the SAW method showed that students A3 (Alternatif 3) had the largest V1 value compared to other alternatifs, which was 3.54. So it can be concluded that A3 are students with the best final scores compared to other students.